These Dogmaticae, Liber II, Theologia Fundamentalis - Heinrichs, Maurus (Typis Typographia Yu-Lien Press, 1942)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage; 6.Yellowing 變黃